Nutrition and Vulnerable Groups - Lawlis, Tanya (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Food insecurity is a complex 'wicked' problem that results from a range of unstable and uncertain physical, social, cultural and economic factors that limits access to nutritious food. Globally, 800 million people are under-nourished, and around 2 billion are overweight/obese or have micronutrient deficiency. These populations are largely positioned in developing countries where disease burden is high and impacts health budgets and productivity. Similarly developed countries, cities and neighbourhoods are experiencing a greater emergence of vulnerable populations. This is in part explained by the change in the food production and manufacturing, the retraction in economic climates, the increase in food price, and in some regions reduced food availability and access.Vulnerable groups include but are not limited to migrant populations, Indigenous people, elderly, pregnant women, those with disability, homeless, young children and youth. Poor nutrition at significant periods of growth and development and during life impact long term health outcomes increasing non-communicable disease prevalence, health cost and reducing economic productivity.